Context and Implications Document for: Sustaining school partnerships: the context of cross‐sectoral collaboration between schools in a separate education system in Northern Ireland. Issue 2 (June 2014) - Duffy, Gavin; Gallagher, Tony
<x xml:space="preserve">Abstract</x> This guide accompanies the following article: Gavin Duffy and Tony Gallagher, Sustaining school partnerships: the context of cross‐sectoral collaboration between schools in a separate education system in Northern Ireland, Review of Education, 10.1002/rev3.3034